Source-sink dynamics facilitate mammal recovery after unsustainable hunting in a community-managed natural protected area in the Peruvian Amazon - Brian M. Griffiths; Ellen Nirenblatt; Chelsie Romulo; Mark Bowler; Fiorella Briceño Huerta; Michael P. Gilmore (Ambio, 2026)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Quantifying erosion susceptibility along a lithologic and trail type gradient (Colorado Front Range, USA) with implications for management - Sharon Bywater-Reyes; Claire E. Lukens; Ara Christine Metz; Chelsie Romulo (CATENA, 2025)

An exploratory study of drawings as a tool to evaluate student understanding of the Food-Energy-Water (FEW) Nexus - Lydia Horne; Amanda Manzanares; Nurcan Atalan-Helicke; Shirley Vincent; Steven W. Anderson; Chelsie L. Romulo (Journal of Environmental Studies and Sciences, 2025)
As future decision-makers, students must develop interdisciplinary, systems thinking skills to make effective management decisions; however, systems thinking remains challenging for many students. Here, we use the Food-Energy-Water (FEW) Nexus as a framework to examine how drawings can help students cultivate systems thinking skills. Drawings can be tools to make implicit mental models of systems connections explicit for instructors to better comprehend student learning. Our goal was to understand how drawing can help students make connections across systems compared to using only verbal explanations. In 2021, we interviewed undergraduates, asking them to draw and verbally explain the FEW Nexus. Analysis revealed that student drawings showed an increase in the number of connections that half of students could describe when compared to verbal-only explanations. Instructors may benefit from this study by recognizing areas where students might struggle to understand FEW Nexus connections, where additional course emphasis is needed, and how drawings can help assess student learning.

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)